Surface coupling effects on the adhesive contact between an elastic solid and a hard substrate with randomly rough, self-affine fractal surfaces. (25th February 2015) - Feshanjerdi, M; Masoudi, A A; Khorrami, M
Abstract: Adhesive contact between an elastic solid and a hard substrate with randomly rough, self-affine fractal surfaces is studied, using an extended version of Persson's contact mechanics theory. It is shown that when both of the surfaces of the adhesive contact are rough, but uncorrelated to each other, the effective interfacial energy is less compared to the case where only the substrate is rough. This is due to the fact that roughness decreases the effective surface areas. When there is a cross correlation between the two surfaces, the effective interfacial energy is different from when there is no cross correlation between two surfaces. It is shown that if the cross correlation between the two surfaces is positive (negative), the effective interfacial energy is larger (smaller) than the case of two uncorrelated rough surfaces.